Social capital modeling in virtual communities : Bayesian belief network approaches - Daniel, Ben Kei, 1971- (Hershey, PA : Information Science Reference, 2009)
'In this book researchers have employed different approaches to examine and describe various types of relationships among people in communities by using social capital as a conceptual and theoretical tool'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Social capital (Sociology); Community development; Technology -- Social aspects; Online social networks